If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(t + 3) + -3(5t + 1) = -13(t + 1) + 2 Reorder the terms: 3(3 + t) + -3(5t + 1) = -13(t + 1) + 2 (3 * 3 + t * 3) + -3(5t + 1) = -13(t + 1) + 2 (9 + 3t) + -3(5t + 1) = -13(t + 1) + 2 Reorder the terms: 9 + 3t + -3(1 + 5t) = -13(t + 1) + 2 9 + 3t + (1 * -3 + 5t * -3) = -13(t + 1) + 2 9 + 3t + (-3 + -15t) = -13(t + 1) + 2 Reorder the terms: 9 + -3 + 3t + -15t = -13(t + 1) + 2 Combine like terms: 9 + -3 = 6 6 + 3t + -15t = -13(t + 1) + 2 Combine like terms: 3t + -15t = -12t 6 + -12t = -13(t + 1) + 2 Reorder the terms: 6 + -12t = -13(1 + t) + 2 6 + -12t = (1 * -13 + t * -13) + 2 6 + -12t = (-13 + -13t) + 2 Reorder the terms: 6 + -12t = -13 + 2 + -13t Combine like terms: -13 + 2 = -11 6 + -12t = -11 + -13t Solving 6 + -12t = -11 + -13t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '13t' to each side of the equation. 6 + -12t + 13t = -11 + -13t + 13t Combine like terms: -12t + 13t = 1t 6 + 1t = -11 + -13t + 13t Combine like terms: -13t + 13t = 0 6 + 1t = -11 + 0 6 + 1t = -11 Add '-6' to each side of the equation. 6 + -6 + 1t = -11 + -6 Combine like terms: 6 + -6 = 0 0 + 1t = -11 + -6 1t = -11 + -6 Combine like terms: -11 + -6 = -17 1t = -17 Divide each side by '1'. t = -17 Simplifying t = -17
| -35x^2-9x+2=0 | | -7(x+1)-17=21+4 | | 3b-33=0 | | 2x^2-600=0 | | 64x^2-69x-2=0 | | 14x=14x+9 | | 3x+4x-7=12 | | 10+2y=2(1x+5) | | 9x-7=5+8x | | 5(n+1)=45 | | 2x+16=4x+4 | | -9c+8=-37 | | 3+6x=36 | | 9x-10=3x+38 | | -6(x+2)-13=22+1 | | -2x=4x+20 | | 1.4-1.6(t+60)=4.6 | | N+3=x-1 | | 6-3*-.4=-18*-.4 | | 5x-3(1x-6)=2 | | 22/6 | | 3x=1+y | | -5(t+9)+4(2t+4)=2(t-8)+6 | | 11-8q=3q-19 | | 6k-25=7-9k | | 6n^2=12n+90 | | 4(4x+1)=116 | | 20x^2-92x-40=0 | | 8-(4n-5)=7-5n | | 7x+3=6x+9 | | 4t^2+19t+21=0 | | 0.12(y-5)+0.02y=0.10y-0.03(30) |